Vertical jumping ability in elite young soccer players - Gerodimos, V.; Manou, V.; Ioakimidis, S.; Perkos, S.; Kellis, S. (Journal of Human Movement Studies, 2006)
The jumping ability of a soccer player. As an expression of power, is a basic factor for good performance in the specific sport. The purpose of the present study was to measure and evaluate the power of the leg extensors muscles in elite young soccer players and its differentiation over age; furthermore. to present indicative values for the vertical jumping ability in elite young soccer athletes during developmental ages.